Analisis Pengaruh Inflasi, PDRB Dan UMP Terhadap Pengangguran Di Pulau Jawa 2017-2020 - Devi Dwi Nuzulaili (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2022)
The purpose of this study was to determine theeffect of Inflation, Gross Regional Domestic Product and Provincial Minimum Wage on Unemployment in Java Island in 2017-2020. Using panel data regression analysis tool with hypothesis testing through the F test, T test and the coefficient of determination R2. The results show that inflation has a significant negative effect where the coefficient value is -0.278630 with a probability value of 0.0190, Gross Regional Domestic Product has a significant positive effect where the coefficient value is 0.894742 with a probability value of 0.0000 and the Provincial Minimum Wage has a significant negative effect where the coefficient value is -1.014373 with a probability value. of 0.0009 of Unemployment in Java Island in 2017-2020. The conclusion of the research is that all variables affect the unemployment variable in Java Island in 2017-2020.